The Relationship between Quality of Work Life (QWL) and the Performance of Honorary Teachers in Public Elementary Schools in West Jakarta: Hubungan Quality of Work Life (QWL) dengan Kinerja Guru Honorer di Sekolah Dasar Negeri Wilayah Jakarta Barat - Nadine Shafira Az-Zahra; Farel Abimanyu Putra (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2026)
This study aims to analyze the relationship between Quality of Work Life (QWL) and the performance of honorary teachers in State Elementary Schools (SDN) in West Jakarta, focusing on the critical urgency of current policy transitions. Employing a quantitative correlational approach, data were collected via questionnaires from a sample of honorary teachers selected through simple random sampling. Data analysis was performed using Pearson correlation and simple linear regression tests. The results indicate that QWL has a positive and significant influence on teacher performance, with a correlation coefficient (r) of 0.671 and a contribution value (R2) of 0.450. However, the dimensions of compensation and job security fell into the low category due to the 2024 honorary teacher restructuring policy ("cleansing") in Jakarta. Despite employment uncertainty, honorary teachers demonstrate unique resilience through stable Organizational Citizenship Behavior (OCB) as a defense mechanism. This study concludes that strengthening QWL through Individual Work Contract (KKI) certainty and fair wages is an absolute prerequisite for educational quality, providing an original model of teacher resilience amidst a staffing crisis.